Bacteriolysis of Streptococcus mutans GS5 by lysozyme, proteases, and sodium thiocyanate. - Wilkens, T J (1982)
Streptococcus mutans GS5 was grown in a synthetic medium containing radioactive thymidine to monitor cell lysis by assay of the release of DNA. Bacteriolysis was achieved by sequential treatment of the cells with either hen egg white lysozyme and sodium thiocyanate or a combination of hen egg white lysozyme and a proteolytic enzyme followed by addition of the thiocyanate. In the absence of sodium thiocyanate, a small percentage of the total macromolecular thymidine was released in control reaction mixtures during incubation. This amount of released DNA more than doubled in trypsin-treated cells, but the inclusion of lysozyme in reaction mixtures prevented assay of the DNA. Lysis was found to be optimal in the late log phase of growth and was dependent on the concentrations of both lysozyme and protease. Concentrations of trypsin or chymotrypsin as low as 0.01 microgram/ml were found to be effective in enhancing the lytic process. The addition of protease to lysozyme-inorganic salt reaction mixtures altered both the pH and ionic strength profiles of cell lysis. At pHs of 5.5 or lower, both the lysozyme-NaSCN and the lysozyme-trypsin-NaSCN systems were inactive in mediating lysis. The loss of insoluble cell wall peptidoglycan by lysozyme treatment was pH independent and did not appear to be affected by the addition of protease. Either diluted whole saliva or neutrophil extracts could replace trypsin to enhance cell lysis further.